ECSCW Ớ"99 Proceedings of the Sixth European Conference on Computer Supported Cooperative Work 12Ớ<U+001c>16 September 1999, Copenhagen, Denmark - B©ıdker, Suanne.; Kyng, Morten.; Schmidt, Kjeld. (Springer Netherlands, 2002)
The emergence of network facilities and the increased availability of personal computer systems over the last decade has seen a growing interest in the use of computers to support cooperative work. This volume contains the proceedings of the sixth European Conference on Computer Supported Cooperative Work (CSCW), a multi-disciplinary area which embraces both the development of new technologies and an understanding of the relationship between technology and society. These proceedings present a collection of papers that encompass activities in the field, treating such subjects as virtual environments, uses of the Internet, studies of cooperative work and emerging models, studies of groupware systems in use in real-world settings, and theories and techniques to support the development of cooperative applications. The articles feature emerging technologies alongside new methods and approaches to the expansion of this important class of applications. Audience: This work reflects the best of the current research and practice within CSCW. It will appeal to both researchers and practitioners whose work involves computer and information science, human-computer interaction, information systems, hypermedia, organisational/social informatics and social studies of science and technology.